Life cycle assessment and economic analysis of Reusable formwork materials considering the circular economy - Ali Tighnavard Balasbaneh; Willy Sher; Mohd Haziman Wan Ibrahim (Ain Shams Engineering Journal, 2024)
Economic development and population growth have impacted on fossil-based energy consumption, contributing to environmental pollution. Adopting circular economy research is more pressing than ever to ease pressure on the environment and the economy. Evaluating the best construction materials is not new. To date, many researchers have assessed materials using various criteria. Formwork differs from other construction materials in terms of serviceability and reusability. These materials may be reused multiple times (from 7 to around 50 times). This raises the question of which material is the best from a sustainability perspective. In this paper we have evaluated four of the most widely-used formwork materials used in the construction of buildings in Malaysia. These include plastic, steel, plywood and timber. Evaluations of life cycle assessment (LCA), embodied energy, and life cycle cost (LCC) were conducted from cradle to cradle. For a single use of formwork, timber is best in all categories except human non-carcinogenic toxicity. However, when 50 reuses are considered for the same wall a completely different result arises. In the environmental category, steel formwork produces the lowest emissions and impact in all categories except global warming potential (GWP). Plastic formwork has the lowest carbon emissions. In terms of embodied energy and cost, plastic formwork presents the best option being approximately 20% lower than steel formwork. Because of the inconsistency in the results for LCA, embodied energy, and LCC for 50-cycles of usage, a multi-criteria decision-making (MCDM) tool was used to normalize the results. The MCDM shows that plastic formwork is an ideal choice for sustainability among the alternatives considered.